Two Volcanic Tsunami Events Caused by Trapdoor Faulting at a Submerged Caldera Near Curtis and Cheeseman Islands in the Kermadec Arc - Osamu Sandanbata; Shingo Watada; Kenji Satake; Hiroo Kanamori; Luis Rivera (Geophysical Research Letters)
Abstract Two submarine earthquakes (Mw 5.8) occurred near volcanic islands, Curtis and Cheeseman, in the Kermadec Arc in 2009 and 2017. Following both earthquakes, similar tsunamis with wave heights of about a meter, larger than expected from their moderate seismic magnitudes, were observed by coastal tide gauges. We investigate the source mechanism for both earthquakes by analyzing tsunami and seismic data of the 2017 event. Tsunami waveform analysis indicates that the earthquake uplifted a submerged caldera around the islands. Combined analysis of tsunami and seismic data suggests that trapdoor faulting, or sudden intra‐caldera fault slip interacted with magma reservoir deformation, occurred due to magma overpressure, possibly in association with caldera resurgence. The earthquake scaling relationship for trapdoor faulting events at three calderas deviates from that for regular earthquakes, possibly due to the fault‐reservoir interaction in calderas.